Enhancing The Writing Ability through Guided Questions Identification Technique by Using Video Clips - Swandi; Mangsih, Raya (La Parole : Journal of Language Teaching and Pedagogy, 2018)
This research is based on the students’ problem regards English, especially in writing. Writing is one of the language skills that should be taught besides the other skills. Based on the curriculum of senior high school recommended by government, there are some texts which have to be mastered by the students at senior high school. One of texts is descriptive text. Descriptive text is the text which describes something, someone, situation and etc. In learning descriptive text the students may have difficulties to express their ideas because they not know how to start and end the paragraph. Therefore, in the writing teaching and learning process needed a good technique and media that researcher interested namely guided questions identification technique by using video clips. Then, the objective of the research is to find out whether or not guided questions identification technique by using video clips able to enhance the writing ability at the tenth year students of SMA Negeri 7 Pinrang. In this research the researcher applied quasi-experimental design, that consisted of experimental class and control class. The population was the tenth year students of SMA Negeri 7 Pinrang. The samples were drawn by using cluster random sampling technique that consisted of 57 students whichwere class X. 2 as an experimental class and class X. 1 as control class. The data were acquired by using writing test. The writing test was applied in pre-test and post-test. The data required for writing test was analyzed by using t-test and percentage technique. The result of the data analysis shows that the students’ writing mastery enhanced. It was shown by the mean score of pre-test is 56.28 and the post-test is 72.14. It shows that through guided questions identification technique by using video clips can enhance the students’ writing ability at the tenth year students of SMA Negeri 7 Pinrang significantly. After analyzing the data by using the test formula, the result of t-test value in post-test is 2.648 and t-table value is 2.004. It means that the t-test value 2.648 is higher than t-table value 2.004. It indicates that H 1 was accepted and H 0 was rejected and the students who were taught through guided questions identification technique by using video clips arebetter than the students who were taught through clustering technique by using video clips.